IMPLEMENTASI PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 54 TAHUN 2005 TENTANG PINJAMAN DAERAH DI KOTA SURAKARTA - Yeni - - (Master of Public Administration, Universitas Slamet Riyadi, 2014)
The purpose of this study was to determine how the implementation of theIndonesian Government Regulation No. 54 the year of 2005 on Debt LocalGovernment. Research site was conducted in General Hospital which is locatedin Surakarta. Government Regulation No. 54 the year of 2005 on debt localgovernment is the main legal basis for any areas that would make loans to localareas. The area is an element loan financing by local governments in carryingout the performance contained in Revenue and Expenditure (Budget). Policyimplementation, however, faces some obstacles that may occur that lead topolicy ineffectiveness. The method used in this study is a qualitative method.Data was coolected by employing interview and document study. Researchwas conducted in Unit of Surakarta Revenue Service Regional Asset WealthManagement, which enables to supply some information concerning theimplementation of regional loan policies. Framework used in this study used themodel of policy implementation proposed by George Edward III. Research resultshows that the communication, resources, disposition and bureaucraticstructure factors greatly affect debt local government policy implementation ofthe project development efforts in General Hospital of Surakarta. Other facorsaffecting are the level of understanding and different capabilities of eachindividual government officials who require uniformity in carrying out the tasksassociated to the implementation of Government Regulation No. 54 On DebtLocal Government.Keywords: debt local goverment, public policy implementation, government regulation.